PREPARATION, CHARACTERIZATION AND ANTI-CORROSION PROPERTIES OF EPOXY-ORGANOBENTONITE COMPOSITE ADDED ZnO SUBMICROMETER PARTICLES - QUOCBINH, BUI; QUOC BINH, BUI (Vietnam Journal of Science and Technology, 2014)
In this paper, an epoxy-based composite coating containing various combinations of zinc oxide submicrometer particles and organobentonite nanoparticles were prepared. Dispersion of zinc oxide particles with organobentonite nanoparticles within the composites were evaluated using XRD analyses. Hardness, adhesion, physical properties and corrosion resistance of composites were studied. The results showed that simultaneous use of low-loading fillers have a positive effect on the clay exfoliation behavior in resulting nanocomposites. Hardness, adhesion of  novel composites containing zinc oxide particle slightly increased compared with neat-epoxy even though with epoxy-organobentonite composite. Corrosion performance of composites increased with addition of zinc oxide and organobentonite particles, due to improving barrier properties of the coating.